2014
DOI: 10.1186/1748-717x-9-48
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of liver protection among 3-D conformal radiotherapy, intensity-modulated radiotherapy and RapidArc for hepatocellular carcinoma

Abstract: PurposeThe analysis was designed to compare dosimetric parameters among 3-D conformal radiotherapy (3DCRT), intensity-modulated radiotherapy (IMRT) and RapidArc (RA) to identify which can achieve the lowest risk of radiation-induced liver disease (RILD) for hepatocellular carcinoma (HCC).MethodsTwenty patients with HCC were enrolled in this study. Dosimetric values for 3DCRT, IMRT, and RA were calculated for total dose of 50 Gy/25f. The percentage of the normal liver volume receiving >40, >30, >20, >10, and >5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…Based on dosimetric comparisons in prostate, liver, and stomach tumours [28][29][30] , RapidArc demonstrated both a high conformal index and the advantages of ptv coverage, results that accord with our analysis. Compared with 3D-crt, RapidArc and imrt showed significant improvements in the conformal and homogeneity indices.…”
Section: Discussionsupporting
confidence: 85%
“…Based on dosimetric comparisons in prostate, liver, and stomach tumours [28][29][30] , RapidArc demonstrated both a high conformal index and the advantages of ptv coverage, results that accord with our analysis. Compared with 3D-crt, RapidArc and imrt showed significant improvements in the conformal and homogeneity indices.…”
Section: Discussionsupporting
confidence: 85%
“…Recent work on the dosimetric consequences of PTV margin size confirms that as the PTV margin decreases, accumulated OAR doses decrease, at the expense of an increased risk of target underdosing 29. The re‐planning strategy outlined in this study mitigated this risk of target miss and preserved the OAR dose sparing gains of small‐margin IMRT for the population as a whole.…”
Section: Discussionmentioning
confidence: 55%
“…Normal liver receiving a dose of more than 15 Gy (V 15 ) was found to be a parameter capable of predicting the deterioration of hepatic function [15]. Moreover, dosimetric studies have found that for liver tumors larger than 8 cm, IMRT or VMAT delivered a higher mean liver dose than 3DCRT [16]. These ndings highlight the di culties of using photon radiotherapy to treat large liver tumors optimally.…”
Section: Discussionmentioning
confidence: 99%